Neurological abnormalities in young adults born preterm. Issue 4 (16th March 2006) - Allin, M; Rooney, M; Griffiths, T; Cuddy, M; Wyatt, J; Rifkin, L; Murray, R
Abstract : Objective: Individuals born before 33 weeks' gestation (very preterm, VPT) have an increased likelihood of neurological abnormality, impaired cognitive function, and reduced academic performance in childhood. It is currently not known whether neurological signs detected in VPT children persist into adulthood or become attenuated by maturation of the CNS. Method: We assessed 153 VPT individuals and 71 term-born controls at 17–18 years old, using a comprehensive neurological examination. This examination divides neurological signs into primary and integrative domains, the former representing the localising signs of classical neurology, and the latter representing signs requiring integration between different neural networks or systems. Integrative signs are sub-divided into three groups: sensory integration, motor confusion, and sequencing. The VPT individuals have been followed up since birth, and neonatal information is available on them, along with the results of neurological assessment at 4 and 8 years of age and neuropsychological assessment at 18 years of age. Results: The total neurology score and primary and integrative scores were significantly increased in VPT young adults compared to term-born controls. Within the integrative domain, sensory integration and motor confusion scores were significantly increased in the VPT group, but sequencing was not significantly different between the VPT and term groups. Integrative neurological abnormalities at 18 were strongly associated with reduced IQ but primary abnormalities were not. Conclusions: Neurological signs are increased in VPT adults compared to term-born controls, and are strongly associated with reduced neuropsychological function.